Peran Ganda Perempuan Dalam Keluarga - Mailod Latuny (Faculty of Law, Universitas Pattimura, 2012)
In modern life, and in today's era of development of Indonesian women demanded andoften motivated to contribute more than that, not limited to husbands care, child care andhousekeeping. Many women are not satisfied in just three roles above, and often familyeconomic circumstances demanded that he work out, or find an activity that can increase thefamily income. The double role of women in the family is to improve the welfare of the family.Woman in the household plays an important role, especially in order to assist and educate thechildren, though it is necessary taps considerable time from a mother to her children. Womenwho work outside the home will also affect domestic life, whether positively or negativelyimpact